Analysis Teacher Understanding on Based Ethnoscience Basic Learning - Rosmeita Ayu Budiarti; Sri Wardani; Arif Widiyatmoko; Putut Marwoto; Woro Sumarni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Development of the globalized world of the 21st century brings many changes, especially advances in the world of education. Ethnoscience-based learning is an innovation that integrates local wisdom as a learning resource to achieve learning objectives. Teachers can connect local wisdom possessed by students and then link it to science learning materials so that learning will be more meaningful and fun. The purpose of this study was to determine the extent of teachers' understanding of ethnoscience-based learning and its application as a learning resource in learning in elementary schools. The sampling technique was purposive sampling from 8 elementary schools, Kaliwungu Kendal. Data were collected by interview, observation and documentation and analyzed by qualitative descriptive method.┬á results of data analysis from 8 resource persons, it shows five from eight teachers have not understood specifically about ethnoscience-based learning, and all teachers have used internal ethnoscience as a learning resource. However, of the 8 teachers, only 3 teachers wrote ethnoscience-based learning designs in the lesson plan. This study aims to determine the skills of teachers in ethnoscience-based learning management.